Adolescents' perceived cost of attending physical education - Ove Østerlie (Cappelen Damm Akademisk NOASP, 2018)
Objective: The purpose of this study was to examine the effect of flipped learning (FL) on adolescents' motivation to participate in physical education (PE) lessons in secondary and upper secondary schools based on adolescents' perceived costs of attending PE. Methods: The students (N=338; 45.3% girls) were recruited from six secondary and upper secondary schools from three different counties in Norway during the spring of 2016. The data were collected using open-ended questions. Results: The data analysis revealed that FL positively affected the adolescents' motivation to participate in PE, as their perceived costs of attending PE significantly reduced, and their intention to participate in PE significantly increased. All the significant changes within the intervention group were explained by gender. The adolescents who reported perceived costs in attending PE were more likely to be unmotivated to attend PE. The perceived costs of attending PE increased with age, and the intention to participate in turn declined. Conclusion: Depending on adolescents' perceived costs of attending PE, FL has a positive effect on their motivation to participate in PE, especially among girls. Thus, FL can be used to enhance adolescents' motivation to participate in PE in secondary and upper secondary schools.